The effect of internal waves on underwater sound propagation - Parnum, Iain; MacLeod, R.; Duncan, Alec; Gavrilov, Alexander (2017)
Knowledge of the undersea environment is critical in estimating ship and submarine performance, estimating ownship susceptibility, and for tactical planning. A major factor determining the detection range of an active sonar system is the sound velocity profile (SVP). Traditionally, the SVP is measured by deploying an XBT (expendable bathythermograph) and converting the temperature profile to an SVP at the location of the ship. Sonar performance is then predicted based on this SVP. However, the ocean is a dynamic environment, and sound propagation conditions can change with both position and time. This study investigated the effect of the variation in the sound velocity profile (SVP) in a dynamic oceanographic region: the Kimberley shelf, where phenomena such as internal waves are present. Temperature and salinity data collected in the Kimberley region, as part of the Integrated Marine Observing System's National Mooring Network, were used to produce SVPs at a sampling interval of 1 minute. These SVPs were then used in a range dependent sound propagation model (RAM Geo). This paper presents the results of this modelling.